The concept of investment on Islam | الإطار الفكري لاستثمار الأموال في الإسلام - Desmadi Saharuddin (Al-Zahra : Journal for Islamic and Arabic Studies, 2008)
Investment is an activity to expand property (almaal).Morever, it is a commitment in managing a sumof money or other sources at present time to gain profitin the future time. Islam encourages this activity inorder to maintain and expand the existing property (almall).In Islam the financial benefit gained frominvestment is not only for the present life but also forthe after life (akhirat). Therefore the investment ethic inIslam is based on norml and morality in accordancewith sharia. The success of investment is not onlydetermined by the improvement of economy andfinancial achieve ment, but also by the moral and ethicstandard based on social and sharia values. Al-Qur'an,al-Hadits and al-Ijtihad become the sorce for theinvestment ethic. This acticle review the concept ofinvestment in Islam m accordance with al-Qur'an,hadits and ijtihad.